2005
DOI: 10.1159/000091445
|View full text |Cite
|
Sign up to set email alerts
|

First Results after Introduction of the Four-Armed da Vinci Surgical System in Fully Robotic Laparoscopic Cholecystectomy

Abstract: Background: Laparoscopic cholecystectomy offers less post-operative pain, less complications, and faster recovery compared with open cholecystectomy. However, laparoscopic surgery can be demanding because of several technical drawbacks. Robotic surgery allows dexterity skills to be performed faster and shortens the learning curve, possibly leading to faster and safer laparoscopic surgery. Methods: In this paper, we report the results of our first 12 cases of fully robotic laparoscopic cholecystectomy using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 36 publications
1
38
0
1
Order By: Relevance
“…These important questions remain unanswered with the current data. Furthermore, the financial cost-benefit should also be considered (Heemskerk et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These important questions remain unanswered with the current data. Furthermore, the financial cost-benefit should also be considered (Heemskerk et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies (Caratozollo et al, 2005, Vidovszky et al, 2006, Ruurda et al, 2002, Chitwood et al, 2001) showed a decrease of the robotic set-up time, but in only 2 studies this decrease was significant (Chitwood et al, 2001;Vidovszky et al, 2006). In one study robotic set-up time did not change in time (Heemskerk et al, 2005) and 2 studies did not report on the robotic set-up time (Perez et al, 2003, Giulianotti et al, 2003.…”
Section: Robot-assisted Laparoscopic Cholecystectomymentioning
confidence: 99%
See 1 more Smart Citation
“…9 Subsequent applications in hip replacement and knee arthroplasty have demonstrated improved results with newer designs. 10,16,19 Applying the da Vinci robotic system, widely used in general surgery and urology, 8 has revealed that the device has limited application…”
Section: Discussionmentioning
confidence: 99%
“…138 For tubal anastomosis, the increase was $1,446. 87 For myomectomy, 93 pyeloplasty, 47 cholecystectomy 64,139 and Nissen fundiplication, 58,140 higher costs were also found for robot-assisted procedure. Most, if not all, cost-effectiveness analyses do not or only partly take into account indirect costs.…”
Section: Cost-effectivenessmentioning
confidence: 99%